Capital structure decisions of european and U.S. listed firms: is there a unique financial theory? - Serrasqueiro, Zélia Maria da Silva (2020)
This study seeks to verify if financial theories are mutually exclusive in explaining the capital structure decisions of European and U.S. listed firms. To achieve the main objective of this study, for the period between 1996 and 2007, a research sample of 659 listed firms made up as follows is taken into consideration: 92 German, 78 Spanish, 95 French, 91 Italian, 76 Dutch, 45 Portuguese, 91 British and 91 U.S. firms. As method of estimation, we use panel data models, namely the GMM System (1998) and LSDVC (2005) dynamic estimators. The results obtained show that for all the listed firms in Europe and the U.S., the existence of a negative relationship between profitability and debt is in accordance with the assumptions of Pecking Order Theory. Furthermore, the negative relationship between liquidity and debt also suggests that European and U.S. listed firms follow the principles of Pecking Order Theory in their capital structure decisions. However, the results also show that European and U.S. listed firms follow the Dynamic Trade-Off Theory seeking to adjust, albeit with different speeds, the level of current debt towards the target debt ratio.